2014
DOI: 10.1177/0741088314526352
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Language Use in the Writing of Developmental Generation 1.5, L1, and L2 Tertiary Students

Abstract: Developmental composition courses serve a sizable and growing number of Generation 1.5 students, or long-term U.S. resident language learners, and it is believed that language challenges may be part of Generation 1.5 writers' difficulty in controlling the academic register. The current study investigates possible similarities and differences between Generation 1.5 students (n = 149) and two other student groups: mainstream first language (L1) writers (n = 203) and more traditional second language (L2) writers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…This is important as these findings show most current writing MOOCs still focus on teaching and learning textual structures, and rely on traditional methods of teaching writing, despite various writing theories. A considerable amount of literature has revealed the phenomena that the practices of teaching writing in face-to-face settings are far removed from writing theories or research (Aull & Lancaster, 2014;Crossley, Roscoe, & McNamara, 2014;Doolan, 2014;Hanauer, 2015;Imbrenda, 2016). It can thus be suggested that the same phenomena were founded in writing MOOCs.…”
Section: Resultsmentioning
confidence: 99%
“…This is important as these findings show most current writing MOOCs still focus on teaching and learning textual structures, and rely on traditional methods of teaching writing, despite various writing theories. A considerable amount of literature has revealed the phenomena that the practices of teaching writing in face-to-face settings are far removed from writing theories or research (Aull & Lancaster, 2014;Crossley, Roscoe, & McNamara, 2014;Doolan, 2014;Hanauer, 2015;Imbrenda, 2016). It can thus be suggested that the same phenomena were founded in writing MOOCs.…”
Section: Resultsmentioning
confidence: 99%
“…The term 1.5 generation was first used in the late 1980s by Rumbaut andIma (1988, cited in Rumbaut, 1994) to refer to individuals who were born in foreign countries and immigrated to the United States before age 12, but it has been used more liberally in the more recent literature (Blumenthal, 2002;de Kleine & Lawton, 2015;Doolan, 2014;Goldschmidt & Miller, 2005;Peña, 2010). Harklau, Losey, and Siegal (1999) explained that characteristics and experiences of this group resemble those of both first generation (foreign-born individuals who immigrated to the United States as adults) and second generation (U.S.-born children of firstgeneration immigrants).…”
Section: Generation 15 Studentsmentioning
confidence: 99%
“…Blumenthal (2002) defines generation 1.5 students as immigrants who "arrive in the United States in their preteen or early teen years and acquire at least some education in U.S. high schools and possibly middle schools" (p. 49). Doolan's (2014) criteria for generation 1.5 are (a) having been in the U.S. education system for more than four years, (b) speaking a language other than English at home, and (c) being younger than 22 years of age. Because there are many developmental stages encompassed in the term, a generation 1.5 immigrant who arrives in the United States at a very young age could have more in common culturally and linguistically with peers who are U.S.-born than with peers who are late-arrival generation 1.5.…”
Section: General Characteristics Of Generation 15 Studentsmentioning
confidence: 99%
See 2 more Smart Citations